2017
DOI: 10.1002/bjs5.5
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide population-based cohort study to assess risk of surgery for adhesive small bowel obstruction following open or laparoscopic rectal cancer resection

Abstract: BackgroundLaparoscopic surgery has been reported to reduce the formation of adhesions following colorectal surgery. The aim of this nationwide cohort study was to investigate the risk of surgery for adhesive small bowel obstruction (SBO) following open and laparoscopic rectal cancer resection.MethodsPatients undergoing rectal cancer resection between 2005 and 2013 were identified in the Danish Colorectal Cancer Group database. The primary outcome of surgery for adhesive SBO was identified in the Danish Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
4
17
0
Order By: Relevance
“…The risk of surgery for SBO has been studied extensively. One study based on data from a Danish registry found this risk to be 4.5% [16], which is the same as that in the present study. Another study found the risk to be between 19 and 66% [17].…”
Section: Discussionsupporting
confidence: 89%
“…The risk of surgery for SBO has been studied extensively. One study based on data from a Danish registry found this risk to be 4.5% [16], which is the same as that in the present study. Another study found the risk to be between 19 and 66% [17].…”
Section: Discussionsupporting
confidence: 89%
“…Although discussion regarding the true readmission rate is ongoing. A population based study, published after the conduction of the survey, showed a slightly lower readmission rate after 5 years (4.5%)[ 13 ] after open surgery. Others report a readmission rate of 6% within 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Others report a readmission rate of 6% within 4 years. But more interestingly is the readmission rate after laparoscopic surgery, which is higher than expected (3.0%)[ 13 ]. So, the positive effect of laparoscopic surgery in comparison to open surgery on adhesion formation seems to be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…SBO is a well-described complication after abdominal surgery and adhesion is considered as the cause of almost 75% SBO, other etiologies including IH, inguinal hernia, incisional hernia, and obstructive tumor etc 30 .…”
Section: Discussionmentioning
confidence: 99%